PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING: (STUDI KASUS PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI ) PERIODE 2021 – 2024) - Benedikta Reinalda Helyanan; Bill Pangayow; Manggalawati Tande Bura (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to analyze the influence of Good Corporate Governance (GCG) and financial performance on Sustainability Reporting disclosure in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The study used a quantitative approach using secondary data from annual reports and sustainability reports. The research sample was determined through purposive sampling, resulting in 10 companies with 40 observations. Sustainability Reporting was measured based on Global Reporting Initiative guidelines, while data analysis used panel data regression. The results showed that Good Corporate Governance and financial performance did not significantly influence Sustainability Reporting disclosure, either partially or simultaneously. This finding suggests that Sustainability Reporting disclosure in pharmaceutical companies remains voluntary and is influenced by factors beyond the research variables.